HADITH TARBAWI IN ISLAMIC EDUCATION: IMPACTS ON 21ST-CENTURY LEARNING READINESS THROUGH CRITICAL THINKING AND RELIGIOUS COMMITMENT - Arcanita, Rapia; Febriyarni, Busra; Destriani, Destriani (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the effect of Hadith Tarbawi utilization on 21st-century learning readiness, mediated by critical thinking and religious commitment. Using a quantitative explanatory design with 218 secondary school students and PLS-SEM analysis, results show that Hadith Tarbawi significantly enhances learning readiness both directly and indirectly. Critical thinking and religious commitment partially mediate this relationship, demonstrating the integration of cognitive and moral dimensions. Findings provide empirical evidence for contextualized Islamic pedagogy that fosters holistic competencies in contemporary education